Predicting Fed Forecasts - R. Ericsson, Neil (Journal of Reviews on Global Economics, 2017)
Monetary policy decisions by the Fed's Federal Open Market Committee have attracted considerable attention in recent years, especially with quantitative easing through large-scale asset purchases, the introduction of forward guidance, and increases in the federal funds rate. The FOMC's decisions are based in part on the Greenbook forecasts, which are economic forecasts produced by the Federal Reserve Board's staff and which are presented to the FOMC prior to their policy meetings. Drawing on Stekler and Symington's (2016) textual analysis of the minutes of the FOMC meetings, the current paper shows that those minutes provide a proximate mechanism for inferring the Fed staff's Greenbook forecasts of the U.S. real GDP growth rate, years before the Greenbook's public release. The FOMC minutes are thus highly informative about a key input to monetary policymaking.